2008
DOI: 10.1007/s00125-008-1080-2
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent requirement of patched homologue 1 in mouse pancreatic beta cell mass

Abstract: Aims/hypothesis Ectopic activation of hedgehog (HH) signalling in pancreas induces various abnormal morphogenetic events in the pancreas. This study analysed the dose-dependent requirement of patched homologue 1 (PTCH1), a negative regulator of HH signalling on pancreatic development. Methods We used a recessive spontaneous mutant mouse denoted as mes which carries a mutated Ptch1 resulting in deletion of the most carboxy-terminal cytoplasmic domain of the PTCH1 protein. In this study, we analysed pancreatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…The expression profiles of hedgehog signaling markers, stem cell markers, and pancreatic A-cell markers at day 8 (PTC), day 14 (PTC, PDX-1, Glut3, and GK), day 17 (IHH, SHH, PTC, PDX-1, Glut2, GK), and day 21 (IHH, PTC, PDX-1, Glut3, GK, and insulin) can be a valuable fundamental model for understanding the time-dependent differentiation process. It has been reported that hedgehog signaling pathway plays an important role in determining the fate of the mesoderm of the gut tube in early pancreatic development, 45 in islet cell function, 46 in pancreatic cancer, and in chronic pancreatitis. 47 Three mammalian hedgehog genes, SHH, IHH, and DHH, have been identified, and their products are found as secreted morphogenetic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The expression profiles of hedgehog signaling markers, stem cell markers, and pancreatic A-cell markers at day 8 (PTC), day 14 (PTC, PDX-1, Glut3, and GK), day 17 (IHH, SHH, PTC, PDX-1, Glut2, GK), and day 21 (IHH, PTC, PDX-1, Glut3, GK, and insulin) can be a valuable fundamental model for understanding the time-dependent differentiation process. It has been reported that hedgehog signaling pathway plays an important role in determining the fate of the mesoderm of the gut tube in early pancreatic development, 45 in islet cell function, 46 in pancreatic cancer, and in chronic pancreatitis. 47 Three mammalian hedgehog genes, SHH, IHH, and DHH, have been identified, and their products are found as secreted morphogenetic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was applied for measurement of the relative area of ␤-cells in the pancreas using the method described previously (19). The following primary antibodies were used: guinea pig antihuman insulin antibody (Linco Research), chicken antihuman insulin antibody (Abcam), guinea pig antip62 antibody (PROGEN), rabbit anticleaved caspase-3 antibody (Cell Signaling Technology), and mouse antihuman Ki67 Ab (BD Biosciences).…”
Section: Immunohistochemical Analysis and Quantification Of ␤-Cell Areamentioning
confidence: 99%
“…Indeed, genetic deletion of the Shh mediator Smo in the pancreas epithelium induces delayed expansion of the early pancreatic epithelium and delayed b-cell mass development (113). Several other studies demonstrate a role of hedgehog signaling in the growth of the pancreas (31,33,34,(114)(115)(116)(117)(118). These seemingly conflicting studies may be consolidated by taking into account the different mechanisms of hedgehog signaling modulation, such as ligand overexpression or Smo deletion.…”
Section: Shh Signaling In Neural and Pancreatic Developmentmentioning
confidence: 99%